Aspek Hukum Pencabutan Hak Asuh Anak dalam Tindak Pidana Penelantaran Anak - Cyntia Yudha Kristanti; Nurul Hudi (Perspektif Hukum, 2018)
This thesis titled "Legal Aspects Of Lifting Of Foster Child Rights In Crime neglect of children". This thesis aims to better understand that any actions of parents who abandon their children dangerous for his son's life in the future. There are several factors that make it more and make children dikhawatiran. Because it will have an impact on the psychology of the child. Therefore Indonesia is still lacking in terms of supervision of child neglect. Most of the problems came from the parents of each family. There are families that are the cause of the onset of delinquency, can be a family that is not normal, state the number of family members who are less profitable.